Design of a SoC based multipurpose, reconfigurable compute unit for nano-satellite applications - Van der Merwe, Jurgen (Stellenbosch : Stellenbosch University, 2025)
van der Merwe, J. 2025. Design of a SoC based multipurpose, reconfigurable compute unit for Nano-satellite applications. Unpublished masters thesis. Stellenbosch: Stellenbosch University [online]. Available: https://scholar.sun.ac.za/items/cb1d6670-8d9e-47b9-bd3e-8d4de05790d6